Molecular Targeting of Acid Ceramidase in Glioblastoma: A Review of Its Role, Potential Treatment, and Challenges - Ha S. Nguyen; Ahmed J. Awad; Saman Shabani; Ninh Doan (MDPI AG, 2018)
Glioblastoma is the most common, malignant primary tumor of the central nervous system. The average prognosis for life expectancy after diagnosis, with the triad of surgery, chemotherapy, and radiation therapy, is less than 1.5 years. Chemotherapy treatment is mostly limited to temozolomide. In this paper, the authors review an emerging, novel drug called acid ceramidase, which targets glioblastoma. Its role in cancer treatment in general, and more specifically, in the treatment of glioblastoma, are discussed. In addition, the authors provide insights on acid ceramidase as a potential druggable target for glioblastoma.